2005
DOI: 10.1159/000084051
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Clearance from Alveolar Spaces of Rat and Human Lungs

Abstract: Background: Although aerosolized β-adrenergic agonists have been used as a therapy for the resolution of pulmonary edema, the mechanisms of catecholamine clearance from the alveolar spaces of the lung are not well known. Objective: To determine whether catecholamine clearance from the alveolar spaces is correlated with the fluid transport capacity of the lung. Methods: Albumin solution containing epinephrine (10–7M) or norepinephrine (10–7M) was instilled into the alveolar spaces of isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
2
5
1
Order By: Relevance
“…In this setup, the rate of ex vivo AFC was significantly reduced in human lobes intratracheally administrated ketamine. Addition of amiloride to the instillate decreased AFC by about 50%, which is in accordance with previous studies [17, 18, 22, 24]. Previous studies showed that S-ketamine via iv at clinically relevant bolus concentrations does not affect AFC in rats [25], the difference might result from the many divergent properties of ENaC between different species.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this setup, the rate of ex vivo AFC was significantly reduced in human lobes intratracheally administrated ketamine. Addition of amiloride to the instillate decreased AFC by about 50%, which is in accordance with previous studies [17, 18, 22, 24]. Previous studies showed that S-ketamine via iv at clinically relevant bolus concentrations does not affect AFC in rats [25], the difference might result from the many divergent properties of ENaC between different species.…”
Section: Discussionsupporting
confidence: 90%
“…Preoperative pulmonary function tests were normal in all patients (see Table 1). The surgical procedure and lung segment chosen were done as described previously [17, 18]. Briefly, immediately after removal of the lung, we occluded the segmental bronchus with a 10-Fr.…”
Section: Methodsmentioning
confidence: 99%
“…This additive effect indicates that adrenergic stimulation acts by an amiloride-independent mechanism. In a previous in vivo study in humans and rats amiloride was shown to change adrenaline alveolar clearance; however, this effect does not apply to our in vitro experiments [11] . In previous animal studies regarding the sodium transport in rabbit experimental hydrothoraces, Zocchi et al [12] also reported that the ␤ -adrenergic influence was amiloride insensitive.…”
contrasting
confidence: 67%
“…Human lung segments were prepared and AFC measurements were done as described previously (27,28). Briefly, the segmental bronchus was occluded by a 10-Fr.…”
Section: Ex Vivo Afc In Human Lungsmentioning
confidence: 99%